Can the Implementation of the Environmental Payment Scheme Increase the National Economic Development in Indonesia? An Empirical Analysis - Yudha, Danang Desta; Pellegrini, Lorenzo (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2017)
This study attempts to investigate the impact of Payment for Environmental Services (PES) on the socioeconomic status of local life. The socio-economic status examined is the total household expenditure to measure the level of nutritional welfare of people living in the area where the PES project is implemented. Not only total household expenditure, but also checking the poverty status of each household in the PES project area. The PES project areas analyzed are villages around Meru Betiri National Park, East Java and Segara Lake, Lombok. This study uses the Social Economy National Surveys (SUSENAS) by Central Beureu from the Central Statistics Agency (BPS), before and after the implementation of two PES implementation projects to examine the effect of PES in each location and the two sites combined. To discuss the impact of PES, this study uses the Difference-in-Difference method and also combines Propensity Score Matching to get better results. it was found that statistically, PES projects had little significant impact on the socioeconomic status of local livelihoods. However, when viewed from the magnitude of the effect coefficient, the evidence shows that PES has positively affected local life. Furthermore, the effects of PES projects differ between each location.